Cultura de segurança do paciente sob a perspectiva das equipes administrativas e de staff - Venancio, Anderson de Jesus (My University, 2023)
This dissertation aimed at identifying and analyzing the Patient Safety Culture of the teams dedicated to administrative and staff care at a highly complex general hospital in southern Brazil. This research, according to Gil (2022), was classified as applied research, considering that it could contribute to solving problems in society. From the perspective of a more general scope, it was explanatory, cross-sectional, and observational and, therefore, a survey based on a quantitative self-report instrument, already validated in Brazil and, internationally, version 1.0 of the HSOPSC - Hospital Survey on Patient Safety Culture, this being the theoretical pillar of the research. The survey was applied using Google Forms, employees with less than three months of employment were excluded, resulting in the participation of 114 people. All of the participants signed the Informed Consent Form and were informed about the risks and benefits of participating in the research. Regarding the analysis of the responses of each of the twelve dimensions, it was identified that there is no strong dimension, nine were classified as potentially strong, and three were considered weak. Composing the result of each dimension, the results of publications on the HSOPSC, applied in several cities in Brazil and the world, as a result of a documentary research, were compared. Concerning the established objectives, the first of them was the identification of the Patient Safety Culture to contribute to the strengthening of the processes of the administrative and staff teams, which was evaluated through the analysis of the research dimensions. The strengths and weaknesses of research on the subject in Brazil and in the world, listed on the Agency for Healthcare Research and Quality (AHRQ) portal, were mapped, which was the second objective. The creation of a technical product was the third objective, given the result of the dimensions, some actions, and plans were formulated. One of them was to create an electronic instrument that guarantees basic information in shift changes at receptions that are open 24 hours a day (patient admission and emergency care); another action was a training method, through a virtual learning environment (Learning Management System - LMS), which workers access on the corporate platform, called MedPortal, customized to meet the target audience, AVASUS video clips and narrated slides were included, making the training journey welcoming. The fourth and final objective was to present a report on the results of the Hospital Survey on Patient Safety Culture (HSOPSC) instrument to the hospital management, which was used to compose a strategic action plan to strengthen the Patient Safety Culture. We must be aware that any of the fragile "links" in the chain, be it the care teams composed of doctors, nurses, physiotherapists, speech therapists, nutritionists, etc., or administrative teams and staff, composed of office assistants, doormen, maids, cleaners, etc., can reflect negatively on the Patient Safety.
Esta dissertação teve como objetivo a identificação e análise da Cultura de Segurança do Paciente das equipes dedicadas ao atendimento administrativo e de staff de um hospital geral de alta complexidade no Sul do Brasil. Esta pesquisa, segundo Gil (2022), se enquadrou como pesquisa aplicada, uma vez que pôde contribuir para a resolução de problemas na sociedade. Do ponto de vista do propósito mais geral, ela foi explicativa, transversal e observacional e, para isso, foi aplicado um survey de um instrumento quantitativo de autorrelato já validado no Brasil e, no plano internacional, a versão 1.0 do HSOPSC - Hospital Survey on Patient Safety Culture, sendo esse o pilar teórico da pesquisa. O survey foi aplicado através do google forms, foram excluídos funcionários com menos três meses de contratação, resultando na participação de 114 pessoas. Todos assinaram o Termo de Consentimento Livre e Esclarecido, receberam orientações sobre os riscos e benefícios ao participar da pesquisa. Sobre as análises das respostas de cada uma das doze dimensões, foi identificado que não há dimensão forte, nove foram classificadas como potencialmente fortes e três foram consideradas fracas. Compondo o resultado de cada dimensão, foi comparado os resultados de publicações sobre o HSOPSC, aplicadas em diversas cidades do Brasil e do mundo, resultado de uma pesquisa documental. Sobre os objetivos estabelecidos, o primeiro deles foi a identificação da cultura de segurança do paciente para contribuir com o fortalecimento dos processos das equipes de atendimento administrativo e de staff, que ocorreu pela análise das dimensões da pesquisa. Foi mapeado os pontos fortes e fracos de pesquisas sobre o tema no Brasil e no mundo, listados no portal da Agency for Healthcare Research and Quality (AHRQ), sendo este o segundo objetivo. A criação do produto técnico foi o terceiro objetivo, diante do resultado das dimensões, algumas ações e planejamentos foram realizados. Uma delas foi criar um instrumento eletrônico que garantisse as informações elementares nas passagens de plantão das recepções que funcionam 24h (internamento e pronto atendimento), outra ação foi um treinamento, através de um ambiente virtual de aprendizagem (Learning Management System - LMS), onde os trabalhadores acessam a plataforma corporativa, chamada MedPortal, customizado para atender o público alvo, foi incluído recortes de vídeos do AVASUS e slides narrados, tornando a jornada de treinamento amigável. O quarto e último objetivo foi a apresentação de um report de resultados do instrumento Hospital Survey on Patient Safety Culture (HSOPSC) para a direção do hospital, o qual foi usado para compor um plano de ação estratégico para fortalecimento da cultura de segurança do paciente. Há de se conscientizar que qualquer um dos "elos" da cadeia que estiverem frágeis, sejam as equipes assistenciais compostas por médicos, enfermeiros, fisioterapeutas, fonoaudiólogos, nutricionistas, etc. ou equipes administrativas de atendimento e staff, compostas por auxiliares de atendimento, porteiros, copeiras, higienizadoras, etc., podem refletir negativamente na segurança do paciente. [resumo fornecido pelo autor]
Keywords: Segurança do paciente; Saúde pública; Pacientes hospitalizados; Patient safety; Public health; Hospital patients